ANALYSIS OF TOTAL DEBT TO ASSET RATIO AND PROFIT MARGIN AS A MEASURE OF COMPANY FINANCIAL PERFORMANCE - Ulfah, Almira Keumala; Nurzianti, Rahma (IAIN Lhokseumawe, 2023)
This research aims to analyze the Total Debt to Asset Ratio (TDTAR) and Profit margin as a measure of a company's financial performance. TDTAR is used to measure a company's debt level in relation to its total assets, while Profit margin is used to measure a company's efficiency in generating net profit from its operating income. These two ratios provide valuable insight into a company's financial condition and profitability. This research identifies that the relationship between TDTAR and Profit margin has important implications in company decision making. A high TDTAR can indicate greater financial risk, especially if it is not balanced with a healthy Profit margin. Conversely, a low Profit margin can indicate operational efficiency problems that need to be corrected. In addition, this research highlights the importance of good financial risk management in managing the relationship between TDTAR and Profit margin. Companies need to understand the impact of these two ratios on their profitability, financial stability and financial decisions. Clear communication with stakeholders is also a key factor in building trust and support. In conclusion, TDTAR and Profit margin analysis are important tools in measuring a company's financial performance. Wise use of these two ratios can help companies plan, manage risks and achieve their financial goals well. This research provides a deeper understanding of the relationship between these two ratios and their implications in the context of corporate decision making.